Urokinase Plasminogen Activator Overexpression Reverses Established Lung Fibrosis - Horowitz, Jeffrey C.; Tschumperlin, Daniel J.; Kim, Kevin K.; Osterholzer, John J.; Subbotina, Natalya; Ajayi, Iyabode O.; Teitz-Tennenbaum, Seagal; Virk, Ammara; Dotson, Megan; Liu, Fei; Sicard, Delphine; Jia, Shijing; Sisson, Thomas H. (Thrombosis and Haemostasis, 2019)
Introduction Impaired plasminogen activation (PA) is causally related to the development of lung fibrosis. Prior studies demonstrate that enhanced PA in the lung limits the severity of scarring following injury and in vitro studies indicate that PA promotes matrix degradation and fibroblast apoptosis. These findings led us to hypothesize that increased PA in an in vivo model would enhance the resolution of established lung fibrosis in conjunction with increased myofibroblast apoptosis.Methods Transgenic C57BL/6 mice with doxycycline inducible lung-specific urokinase plasminogen activator (uPA) expression or littermate controls were treated (day 0) with bleomycin or saline. Doxycycline was initiated on days 1, 9, 14, or 21. Lung fibrosis, stiffness, apoptosis, epithelial barrier integrity, and inflammation were assessed.Results Protection from fibrosis with uPA upregulation from day 1 through day 28 was associated with reduced parenchymal stiffness as determined by atomic force microscopy. Initiation of uPA expression beginning in the late inflammatory or the early fibrotic phase reduced stiffness and fibrosis at day 28. Induction of uPA activity in mice with established fibrosis decreased lung collagen and lung stiffness while increasing myofibroblast apoptosis. Upregulation of uPA did not alter lung inflammation but was associated with improved epithelial cell homeostasis.Conclusion Restoring intrapulmonary PA activity diminishes lung fibrogenesis and enhances the resolution of established lung fibrosis. This PA-mediated resolution is associated with increased myofibroblast apoptosis and improved epithelial cell homeostasis. These studies support the potential capacity of the lung to resolve existing scar in murine models.
Keywords: myofibroblast; apoptosis; plasminogen activators; wound healing; pulmonary fibrosis